Penerapan Metode Bernyanyi Dalam Menguatkan Daya Ingat Pada Mata Pelajaran Akidah Akhlak - Miski Arsyani; Fajar Syarif (Prodi Pendidikan Keagamaan Islam, 2024)
In the world of education, learning methods are very important to help students understand and remember information well. We often encounter many teachers who still use learning methods such as lectures and textbook readings which cause learning to seem monotonous, thus causing a decrease in student activeness in the teaching and learning process, lack of enthusiasm, and even feel bored causing students to be busy with their own world. With this problem, the researcher felt interested in discussing the application of the singing method in strengthening memory as a more creative and interactive approach. The main purpose of this study is to determine the application of the singing method in strengthening memory in Akidah Akhlak subjects at Madrasah Ibtidaiyah Istiqlal Jakarta. This research uses a type of qualitative research method with a descriptive approach. The primary data in this study amounted to 5 people including the head of the madrasa, the moral creed subject teacher, and three students. While secondary data is obtained from books or journals. Data collection techniques used by researchers in obtaining information are observation, interviews, and documentation. The data analysis technique used is three stages, namely data reduction, data presentation, and conclusion drawing or verification. The results showed that the application of the singing method in the subject of moral creed has a positive impact in strengthening students' memory through repetition of information that is fun and relevant between lyrics and material. This method is proven effective in increasing student involvement during the learning process.